The roles of teachers in enhancing effective classroom management strategies in Gauteng high schools, South Africa - Omodan, Bunmi Isaiah; Mamaile, Dineo (Nurture, 2024)
Purpose: This study explores the challenges teachers face in their classroom management roles which are essential for fostering a supportive learning environment. It investigates teachers' roles in implementing management strategies and the obstacles hindering their effectiveness in high schools. Design/Methodology/Approach: The present study used semi-structured interviews to collect data from twelve Grade 10 teachers in three selected secondary schools located in the Ekurhuleni North District of Gauteng Province, South Africa. The data were interpreted using a phenomenological research design and interpretive paradigm. The study was based on ecological systems theory. Thematic analysis was used to make sense of the data. Findings: The study revealed that key roles of teachers in effective classroom management include appropriate classroom language, acting as managers and self-criticism and evaluation of performance. However, challenges such as insufficient teaching and learning resources and the low academic ability of learners impede the fulfilment of these roles. Conclusion: The study finds that continuous self-criticism and evaluation are critical for improving teaching and learning processes, although teachers play a critical role in monitoring classrooms and resolving difficulties imposed by low academic competence. Recommendations: Recommendations include comprehensive training and support for teachers, the implementation of diverse teaching strategies and a holistic consideration of the ecological system encompassing both learners and teachers.